Water-based LiNi1/3Mn1/3Co1/3O2-cathodes with good electrochemical performance by use of additives. (10th January 2018) - Memm, Michaela; Hoffmann, Alice; Wohlfahrt-Mehrens, Margret
Abstract: The manufacture of lithium nickel manganese cobalt oxides (NMC) suspensions for cathodes is typically performed with organic solvents like N-methyl-pyrrolidone (NMP) or N-ethyl-2-pyrrolidone (NEP). It is widely known that these substances are caustic and toxic to reproduction. The utilization of water for the preparation of a cathode suspension is less hazardous and saves costs. Unfortunately NMC alkalinizes the water to a very pH value, which leads to a pit corrosion of the aluminum substrate. The development and optimization of water-based NMC suspensions therefore must include investigations on lowering the pH value without deteriorating the electrochemical performance of the material. One option is the addition of amphoteric oxidic additives. This work focusses on Al2 O3 and SiO2 as additives and explores their effects on the pH of the suspension and on the substrate corrosion as well as on the electrochemical performance of the NMC-cathode prepared therefrom. Furthermore the impact of the particle sizes of the additives was studied.